Petrophysics theory and practice of measuring reservoir rock and fluid transport properties - Tiab, Djebbar (Gulf Professional, 2011)
This new edition includes updated case studies, examples and experiments as well as a new chapter on modeling and simulations. It also includes recent advances in wireline logging interpretation methods, effective media models, inversion of resistivity log measurements, dipole acoustic shear and Stoneley wave techniques, Biot-Gassmann models and MRI. Comprehensive but easy to use New case studies, exercises and worked examples A 30% update over the second edition Techniques for conducting competent quick-look evaluations Online component with step-by-step calculations, modeling and simulations, and experiments.
Previous ed.: 2003.
Keywords: Petroleum -- Geology.; Petrology.; elektronické knihy; electronic books